The application of CSR in marketing communication and its potential impact on customer perceived value - Michal Ruschak; Zdeněk Caha; Milan Talíř; Michal Konečný (Entrepreneurship and Sustainability Issues, 2023)
The research aims to determine whether companies using CSR in their marketing communication believe this approach has a positive effect on CPV and what forms of communication mix they most often use for this purpose. To achieve this goal, the method of online questionnaire survey was selected for data collection. The methods of correlation and regression analysis and structural equation modelling were used for data processing. Results obtained by interviewing business representatives show that companies often need to realize these are CSR principles to implement CSR activities. The most commonly used CSR communication tools include "Public relations & publicity" and "Internet marketing"; however, no statistically important correlation between these tools has been confirmed. The research results confirm that companies using CSR for marketing communication are aware of its importance concerning the brand's positive perception; on the other hand, from the perspective of the interviewed companies, no link between CSR, its communication, and the company's reputation has been confirmed. Companies might not be aware of the benefits the implementation of CSR and CSR communication may bring. Based on the research results, it can also be confirmed that the communication tools most commonly used by the companies that perceive the connection between CSR and CVP are online, i.e., digital marketing. The benefits of the research for practice consist in recommending the application of CSR-related marketing communication tools regularly and appropriately in the long run. Another recommendation is the targeted working with companies' reputation and promoting the good name of the brand. It shows that CSR communication can effectively build a brand's reputation, image, and identity. The results show that business representatives might need to be aware of all these benefits, including the potential impact on CPV.